1981
DOI: 10.1021/i300004a013
|View full text |Cite
|
Sign up to set email alerts
|

Hydroisomerization and hydrocracking. 2. Product distributions from n-decane and n-dodecane

Abstract: The hydroisomerization and hydrocracking of n-decane and n-dodecane on an ultrastable zeolite Y, containing 0.5 wt % platinum, at T = 130-250 °C and P = 5-100 bar was Investigated. The product distributions are a unique function of the total conversion only and are typical for a carbenium ion mechanism. Primary products are the monobranched isomers of the n-alkane feed. Multibranched feed isomers and cracked products are formed in consecutive reactions. Secondary cracking reactions start at high conversion lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 186 publications
(114 citation statements)
references
References 3 publications
8
106
0
Order By: Relevance
“…Ammonium or sodium forms of the zeolite samples were prepared by repeated ion exchange with 0.5 M ammonium or sodium chloride solutions (25 ml/g), pH value of 7.5-8 was adjusted with ammonia and NaOH solution, respectively. Subsequently, nickel ions were incorporated into the Na-and NH 4 -zeolites by ion exchange with 0.08 molar nickel acetate solution at room temperature or 340 K for 5h. Then the samples were washed with water, and dried at about 353 K. The chemical compositions of the prepared samples are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ammonium or sodium forms of the zeolite samples were prepared by repeated ion exchange with 0.5 M ammonium or sodium chloride solutions (25 ml/g), pH value of 7.5-8 was adjusted with ammonia and NaOH solution, respectively. Subsequently, nickel ions were incorporated into the Na-and NH 4 -zeolites by ion exchange with 0.08 molar nickel acetate solution at room temperature or 340 K for 5h. Then the samples were washed with water, and dried at about 353 K. The chemical compositions of the prepared samples are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This Dn OH shift of 88 cm -1 was found for all BEA zeolites independently from their framework boron contents. Since Dn OH reflects the deprotonation energy of the OH group [16], it can be concluded that in BEA zeolites bridged hydroxyls associated with Al(OSi) 4 units are, independently of co-existing framework boron, of the same intrinsic acid strength. The intrinsic acid strength was also not affected by incorporation of sodium cations by ion exchange up to exchange levels of 50-60 % (spectra are not shown).…”
Section: Acidity Of Parent Bea Zeolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, Weitkamp and coworkers have investigated product distribution, with an insight into isomers composition. [1][2][3][4] These works are outstanding in the definition of the HDK reaction mechanism, mainly concerning the formation of branched products and CAC bond scission pattern. Later, Froment and coworkers focused on the development of a kinetic model for the HDK reaction of model compounds.…”
Section: Introductionmentioning
confidence: 99%